2018
DOI: 10.19159/tutad.342885
|View full text |Cite
|
Sign up to set email alerts
|

Diyarbakır’da Buğday Ürününe Karışan Yabancı Ot Tohumlarının Belirlenmesi

Abstract: Bu araştırma hasat edilen buğday ürünü içerisine karışan yabancı ot tohumlarının belirlenmesi amacıyla Diyarbakır ilinde 2017 yılında yapılmıştır. Bu amaçla buğday tarımının yoğun yapıldığı 10 ilçedeki buğday ürünlerinden 100 örnek alınmıştır. Toplanan örnekler eleklerden (6-60 mesh) geçirilmek suretiyle içerisinde bulunan kaba ve cansız materyali alınmış, kalan kısımdaki yabancı ot tohumları ayrılmıştır. Yabancı ot tohumları binoküler mikroskop altında incelenerek tür teşhisleri gerçekleştirilmiştir. Diyarbak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In order to determine the amount of products taken into the sifting process, it starts with the calculation of the area(A) they occupy on the counter. Area calculation for the quantity of products according to the images obtained from the camera; it depends on the horizontal axis pixel number ( 𝑀 𝑥 ) of the computer monitor, the vertical axis pixel number (𝑀 𝑦 ), the actual lengths of the horizontal axis(𝐶 𝑥 ) and vertical axis(𝐶 𝑦 ) of the bench area viewed by the camera, and the total number of pixels(𝑃 𝑛 ) occupied by the products in the sifting process (1). The pollution/conformity(𝑃 𝑟 ) ratio of the agricultural products taken into the sifting process depends on the number of detected foreign matter/inappropriate agricultural product (𝐹 𝑛 ), the amount of the products taken into the sifting process (A) and a pollution coefficient (𝑃 𝑐 )(2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to determine the amount of products taken into the sifting process, it starts with the calculation of the area(A) they occupy on the counter. Area calculation for the quantity of products according to the images obtained from the camera; it depends on the horizontal axis pixel number ( 𝑀 𝑥 ) of the computer monitor, the vertical axis pixel number (𝑀 𝑦 ), the actual lengths of the horizontal axis(𝐶 𝑥 ) and vertical axis(𝐶 𝑦 ) of the bench area viewed by the camera, and the total number of pixels(𝑃 𝑛 ) occupied by the products in the sifting process (1). The pollution/conformity(𝑃 𝑟 ) ratio of the agricultural products taken into the sifting process depends on the number of detected foreign matter/inappropriate agricultural product (𝐹 𝑛 ), the amount of the products taken into the sifting process (A) and a pollution coefficient (𝑃 𝑐 )(2).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, there are other plant seeds mixed into the product collected in the field, which is undesirable [1][2][3][4][5][6][7][8]. For this, it should be ensured that the right taste and desired quality food products are obtained by selecting processes.…”
Section: Introductionmentioning
confidence: 99%
“…They found that Adonis sp., Ranunculus arvensis and G. tricornutum were heavily contaminated in the Eastern Black Sea Region. Pala et al (2018) determined that the weed seeds were most intensely contaminated into the harvested wheat product belonged to the Poaceae family with 13 species. It was determined that the most common species were Avena fatua and A. sterilis in Diyarbakır province.…”
Section: Intrоduсtiоnmentioning
confidence: 99%
“…It ranks third in Turkey in terms of wheat production. Diyarbakir province ranks fourth in Turkey in terms of wheat cultivation area (264000 ha, with 3.3% share), and ranks third in terms of production (845000 tons, with 4.2% share) (Pala et al 2018).…”
Section: Introductionmentioning
confidence: 99%